The Idea of Ancient India : Essays on Religion, Politics, and Archaeology - Upinder Singh (Sage, 2016)
"This book engages with some of the most important issues, debates, and methodologies in the writings of ancient Indian history. Thematically structured into four sections, it critically addresses how the material remains of India's early past were discovered and understood in colonial and post-colonial times. The first section highlights the importance of a thorough empirical approach for understanding the process of social history and early medieval state formation. The second connects ancient and modern India, based extensively on archival sources. The third and fourth sections emphasize the important issue of ancient Indian intellectual history, underlining the significance of reconstructing the intellectual landscape of ancient India through a sensitive and yet critical historicization of its texts and inscriptions"--Provided by publisher.